Innovative reflections on the visual language of batik in the Bouyei ethnic group of Guizhou, China - Liu, Yang Yi; Shaari, Nazlina; Mohd Ali, Noor Azizi; Perumal, Velu (Redfame Publishing, 2022)
Intangible cultural heritage should not only be inherited and protected but also developed and innovated. Only in this way can traditional cultural heritage keep pace with the times and fully demonstrate its value and significance, and the Guizhou Bouyei batik is no exception. Batik is one of China's ancient folk traditional printing and dyeing processes. It is a common dyeing process and an intangible cultural heritage of ancient China. The art of batik is a time-tested craft. The technique of batik has more than one hundred years, during which it has become more and more complicated and improved. Guizhou is known as the birthplace of batik. Batik is an important symbol of Guizhou that can be traced back to the Qin and Han Dynasties. Guizhou Province is the main population center of the Bouyei ethnic group in China. The visual language is the overall display of the artistic design effect, and the Guizhou Bouyei batik has artistic attributes. Through the innovation of batik materials, technical methods, forms of expression and inheritance, the innovation of visual language will eventually lead to the formation of a new look of batik of Bouyei Nationality in Guizhou.